PENERAPAN PEMBELAJARAN DENGAN STRATEGI REACT UNTUK MENINGKATKAN AKTIVITAS BELAJAR MATEMATIKA - Imam Wahyudi (Saintifika, 2018)
Abstract: This research question is How do steps with REACT strategy to improve the students learning activity?. The learning impleentation with REACT strategy had threes steps which are:1) Opening, 2) Main, 3) Clossing. The result of this research showed that the students learning activities improved from cycle I to cycle II which is 18.62% from 67.00% in cycle one become 85.62% in cycle two. The other result of this research is the improved 15% which is from 75% in cycle I to 90% in cycle II. Based on the result of analysis known that using REACT strategy learning not only improve the students learning activities but also improve the student achievement. It is caused by the meaningful learning activity. So the students will well understand the concept of the learning material.